BLENDED LEARNING DESIGN FOR BLOCK SYSTEM PRACTICUM ON ELECTRICAL ENGINE COURSE AT STATE UNIVERSITY OF MALANG - Erwin Komara Mindarta; Eddy Sutadji; Andika Bagus Nur Rahma Putra (Erudio Journal of Educational Innovation, 2018)
All this time, the form of web-based learning implementation has brought optimal learning process. Yet, it requires an instructional design as a learning model that can be liked by the students to engage in various learning activities such as discussions, frequently asked questions, and learning process requests that require face-to-face learning. The blended learning design is developed based on ten methods of learning model design of Gerlach and Ely. Furthermore, it can be developed into learning steps (syntax) of blended learning.